New Green Luffa-Based Biosorbent for Solid Phase Extraction (Luffa-Spe) of Seven Polycyclic Aromatic Hydrocarbons in Water Samples - Toledo-Neira, C; Toledo-Neira, C; Garrido-Morales, F; Garrido-Morales, F; Berrios-Guinez, C (Elsevier B.V., 2026)
Luffa sponge is a natural fiber composed of cellulose, hemicellulose and lignin. This material has large contact surface, and is inexpensive and biodegradable, which gives it properties that make it a good candidate for biosorbent in analyte extraction processes. This study investigated the feasibility of applying Luffa as a biosorbent for the extraction of seven Polycyclic Aromatic Hydrocarbons in aqueous matrices and their subsequent quantification by high-performance liquid chromatography with fluorescence detector. The preparation of the biosorbent was carried out by functionalizing Luffa with stearic acid to obtain a hydrophobic sorbent. The extraction parameters-such as biosorbent mass, sample volume, and elution volume, were carefully optimized by univariate analysis. The optimal conditions were 0.8 g of biosorbent, 50 mL of sample and 7.5 mL of elution volume. Good analytical performance was achieved with limits of detection between 2 and 3 μg L−1 and limits of quantification between 5 and 11 μg L−1 for the studied analytes. Absolute recoveries ranged from 72 % to 88 % for all analytes, with standard deviations below 5 % and enrichment factors between 11 and 30. The efficient and sustainable method was applied to the simultaneous extraction and determination of seven Polycyclic Aromatic Hydrocarbons in environmental water samples, finding levels between 3 and 29 μg L−1 for the total amount of analytes studied. The results demonstrated the great potential of this new phase for the efficient and sensitive extraction of hydrophobic analytes, as Polycyclic Aromatic Hydrocarbons, in environmental water samples. © 2025
Keywords: Luffa; Stearic acid; Biosorbent; Polycyclic Aromatic Hydrocarbons; Solid phase extraction; Natural water samples